Studies on Oil Palm Based Cropping Systems in Ghana - Nuertey, B.N. (University of Ghana, 1999)
A survey was conducted in 1994 to gather information on the practice of intercropping food crops in oil palm on small-scale farms in the oil palm zones of southern Ghana. The objective was to identify and study intercropping systems used in oil palm production. Data was collected by interviewing a total of 72 oil palm farmers from the oil palm growingregions,(Eastern, Central,Western,Ashanti,Brong-Ahafo,and Volta) at their farm locations. The responses indicated that the small-scale oil palm farmers in Ghana commonly intercrop oil palm with maize, cassava and plantain especially during the first three years of the crop. The three staple crops, maize, cassava and plantain were intercropped in oil palm between 1994 and 1997 at the Oil Palm Research Institute, Kusi, Ghana to assess their effects on the growth, development and yields of oil palm. Intercropping was compared to the standard system of cover cropping oil palm with pueraria. XV111 v.fIS/ Nutrient dynamics, soil moisture retention, and solar interception by the oil palm were also examined. The performances of the food crops were also assessed as well as the ability of the cropping systems to control weeds was assessed. An economic analysis was also carried out. There were seven treatments, consisting of: (i) sole oil palm with pueraria cover crop; (v-vii) sole crops of maize, cassava and plantain respectively. These were arranged in a randomnized complete block design and replicated four times. Intercropping oil palm with maize, cassava and plantain had no adverse effect on the growth, development and yield of the oil palm. The Oil palm + maize + maize intercrop and oil palm cover- cropped with pueraria positively influenced soil moisture retention, nutrient uptake and accumulation and light interception by the oil palm more than what pertained with oil palm + maize + cassava and oil palm + maize + plantain. (iii) oil palm + maize + plantain (ii) oil palm + maize + cassava; (iv) oil palm + maize + maize; Yields of the intercropped food crops compared favourably with yields of these crops when solely cropped. The sole oil palm with pueraria cover crop and oil palm + maize + maize association controlled weeds better than the oil palm + maize + cassava and oil palm + maize + plantain associations. Intercropping oil palm with maize, cassava and plantain was found to be economically beneficial to the small-scale oil palm farmer.
Thesis (PHD) - University of Ghana, 1999